Si Carancal laban sa kidlat Carancal versus the lightning - Villanueva, Rene O.; Albano, Kora Dandan; Pastor, Boots S. Agbayani (Quezon City Lampara Publishing House, Inc., 2009)
In this story, Carancal has to deal with lightning, and once again exhibits resourcefulness and shows diplomacy in dealing with problems, likewise his concern for the welfare and safety of others.
Text in English and Filipino.
Keywords: Folklore -- Philippines